2021
DOI: 10.1590/0102-311x00182720
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Brazilians’ self-rated health during the COVID-19 pandemic

Abstract: This is a cross-sectional study investigating the factors affecting brazilians’ self-rated health during the COVID-19 pandemic, based on data from the web-based behavior survey. Carried out from April 24 to May 24, 2020, the survey recruited participants by a chain sampling procedure. Its outcome was the worsening of self-rated health during the pandemic. Statistical analysis was based on a hierarchical model of determination. Logistic regression models were used to test the associations between sociodemograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0
25

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 33 publications
5
24
0
25
Order By: Relevance
“…These results were found in a previous study with mining workers in the same region as this study; when evaluating sleep using the gold standard method, polysomnography, the workers with hypovitaminosis D had lower sleep efficiency, an increased microarousal index, and lower arterial oxygen saturation after adjusting for seasonality, age, and body fat (Menezes- Júnior et al 2021). These workers had routines similar to confinement during the COVID-19 pandemic, since they were off-highway truck drivers and spent most of their time in machines inaccessible to sunlight (Menezes Júnior et al 2021).…”
Section: Discussionsupporting
confidence: 87%
“…These results were found in a previous study with mining workers in the same region as this study; when evaluating sleep using the gold standard method, polysomnography, the workers with hypovitaminosis D had lower sleep efficiency, an increased microarousal index, and lower arterial oxygen saturation after adjusting for seasonality, age, and body fat (Menezes- Júnior et al 2021). These workers had routines similar to confinement during the COVID-19 pandemic, since they were off-highway truck drivers and spent most of their time in machines inaccessible to sunlight (Menezes Júnior et al 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Results of the first stage of the ConVid-Behavior Survey carried out in the Brazilian adult population have shown the negative impact of pandemic-related social restraint measures on the overall health of citizens who have been affected by psychological health problems [14,15]. However, there were differences in the results by age group, with older adults (60 years or over) reporting less anxiety, sadness, and loneliness in comparison to the youngest group (18-29 years old).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of back pain among teachers during the pandemic period covered by this study had 57.7% of prevalence. For the Brazilian population in general, 27.1% of adults interviewed reported that they started experiencing back pain during the COVID-19 pandemic (Szwarcwald et al 2021b ). Among Italian workers in the administrative sector, 50% reported the worsening of neck pain and 38.1% the worsening of low back pain since they started working remotely with the onset of the pandemic (Moretti et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the literature that distinguishes self-rated health as an indicator of the individual’s general health, including musculoskeletal aspects (Andrade et al 2019 ; Pavão et al 2013 ); and it also indicates sleep disorders as a risk factor for chronic musculoskeletal pain (Chun et al 2018 ; Mork et al 2013 ). A study that investigated factors that affected the self-rated health of Brazilians found an association between the worsening self-rated health and the emergence of back pain during the COVID-19 pandemic (Szwarcwald et al 2021b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation